2019
DOI: 10.1111/anae.14966
|View full text |Cite
|
Sign up to set email alerts
|

Choice of local anaesthetic for epidural caesarean section: a Bayesian network meta‐analysis

Abstract: Summary Rapid‐onset epidural local anaesthesia can avoid general anaesthesia for caesarean delivery. We performed a Bayesian network meta‐analysis of direct and indirect comparisons to rank speed of onset of the six local anaesthetics most often used epidurally for surgical anaesthesia for caesarean delivery. We searched Google Scholar, PubMed, EMBASE, Ovid, CINAHL and CENTRAL to June 2019. We analysed 24 randomised controlled trials with 1280 women. The mean (95%CrI) onset after bupivacaine 0.5% was 19.8 (17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
1
24
2
Order By: Relevance
“…The goal of the present prospective audit of practice was to evaluate the incidence of breakthrough pain anesthetics, usually a fast onset drug combined with a longer acting drug, increase the risk of breakthrough pain because they lose their potential when mixed together (the dose of the long acting local anesthetic is too low). These results are in line with previous reports 15,16 . All other potential factors that have been reported to be risk factors for breakthrough pain, were not confirmed in our cohort.…”
Section: Discussionsupporting
confidence: 94%
“…The goal of the present prospective audit of practice was to evaluate the incidence of breakthrough pain anesthetics, usually a fast onset drug combined with a longer acting drug, increase the risk of breakthrough pain because they lose their potential when mixed together (the dose of the long acting local anesthetic is too low). These results are in line with previous reports 15,16 . All other potential factors that have been reported to be risk factors for breakthrough pain, were not confirmed in our cohort.…”
Section: Discussionsupporting
confidence: 94%
“…9,23 A recent Bayesian network meta-analysis including 24 randomized clinical trials reported the rank order of EA onset for cesarean section with 2% lidocaine plus bicarbonate as the fastest, followed by 3% 2-chloroprocaine and 2% lidocaine. 24 Ituk et al found that the onset times of 2% lidocaine with epinephrine and 3% chloroprocaine were 10-12 min and 3-5 min, respectively, when extending labor analgesia to anesthesia. 9 Few direct comparisons of the onset time of lidocaine and chloroprocaine in labor EA are available.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the incidences of hypotension in parturients who underwent a cesarean section were 32–52% after EA, 43–64% after SA, and 32–70% after CES ( 8 11 , 20 22 , 26 ). In present study, the incidences of hypotension after neuraxial anesthesia were ~58 and 40% in parturients with and without COVID-19, respectively.…”
Section: Discussionmentioning
confidence: 99%